PROGRAM OF GUIDANCE FOR PREVENTION AND CONTROL OF THE YOUTH OBESITY: A STUDY CASE (Fiep Bulletin - online, 2014)
This study is featured as a case study whose primary objective is to develop a protocol of an interdisciplinary program capable of promoting changes in behavior and indicators in young people with overweight or obesity. The initial proposal was focused on body weight, information, motivation and creating opportunities for change in lifestyle. The initial group was made up of 21 young people aged between 14 and 19 years of age for both sexes. These volunteers were selected by their BMI (Body Mass Index) that according to the table proposed by the International Obesity Task Force of the World Health Organization (WHO), which takes into account the age and sex of children young. The population selected participated in a program of action that includes weekly meetings in a period of four months, with the participation of a multi professional team: physical education professionals, nutritionist, psychologist, cardiologist and an endocrinologist. The data were collected in COAFIS (Guidance Center for Physical Activity and Health) of UFSC, where the project was developed, but the laboratory tests have been made in the University Hospital of UFSC. The assessment includes the following information: a) personal and family data, b) Physical Examination, c) assessment related to the health and fitness physical activity usual, d) evaluation Endocrinology and), psychological evaluation, f), evaluation of the food consumption. The first step was developed in the second half of 2003. The activities of this phase follow all the specifications that the project requires, from the selection of volunteers, the assessments and also the control and the orientation program, which was developed over a period of four months of intervention, with four hours per week. This project therefore emphasized the priority development of a protocol for intervention interdisciplinary, noting the difficulties of implementation, results and the changes of behavior and indicators of obesity.
Keywords: Young; interdisciplinary program; change of behavior